The Impact of Colonialism in Hugh Lofting’s The Story of Doctor Dolittle - Raden Alexander Carlson Medicio; Nur Saktiningrum (Universitas Gadjah Mada, 2023)
The Story of Doctor Dolittle is the first entry in the Doctor Dolittle series, a children’s book series by English author Hugh Lofting. Despite being primarily aimed at children, the series contains mature themes that help it attract the attention of adults. In particular, The Story of Doctor Dolittle contains themes of colonialism that are drawn from the author’s own experiences. This research aims to discover how colonialism in The Story of Doctor Dolittle has impacted the numerous characters found in it. The original 1920 publication of the book was used as the primary data source, in which it was analyzed using a thorough closed reading of its contents, which is then compared with real-life colonial events. Jurgen Osterhammel’s theory of colonialism is used as the primary theory for this research, which details the processes and results of colonialism on both the colonizers and the colonized, as well as the different types of colonies created to serve different purposes for the colonizers. The results have shown that there are multiple instances of colonialism in The Story of Doctor Dolittle, both positive and negative, that have impacted its characters to varying degrees. Characters such as Doctor Dolittle and the monkeys of the Land of the Monkeys benefited from colonialism due to the former’s altruistic motives, while others like the Jolliginki tribe suffered due to reckless exploitation by the unnamed White Man.